Meningkatkan Kesadaran Sosial Anak SD melalui Program Anti-Bullying - Eliya Astuti; Nenda Jestiliana; Indah Purnama Sari; Muhammad Apriliansyah Rahmadhani; Riki Adriant (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
The Anti-Bullying Program in Sinar Bhakti Village, Ogan Komering Ulu Regency aims to raise social awareness among elementary school children about the impact of bullying and the importance of social solidarity in the school environment. This community service uses a qualitative analysis method with a case study approach on elementary school children involved in the program. Data was collected through presentations and question-and-answer sessions with the students participating in the program, as well as observations of changes in their attitudes and social interactions during and after the program. This program is designed to provide a deeper understanding of bullying, both from the perspective of victims and perpetrators, and how it impacts individuals and communities. The results of this community service show that the program successfully increased students' understanding of bullying behavior and its effects on psychological, social, and emotional well-being. Additionally, the program strengthened empathy, cooperation, and solidarity among the students in Sinar Bhakti Village, as reflected in the positive changes in their social interactions, which became more inclusive and supportive. Most students who were previously unaware of the impact of bullying now recognize that such behavior is unacceptable in their social life. This program has proven effective in fostering a more positive anti-bullying culture among elementary school children in Sinar Bhakti Village and contributed significantly to the improvement of social awareness in their community.